(untitled) (The International Journal for Scientific Research, 2024)
This study explores the impact of applying Agile methodology on performance quality and project duration within the NEOM project, which represents one of the largest and most complex projects in Saudi Arabia. The study analyzes the effect of Agile implementation based on data collected through surveys and interviews with a diverse group of project stakeholders. The study was divided into several phases, starting with understanding how Agile methodology was applied in the project and assessing participant satisfaction with the methodology. Analysis of the data revealed that Agile implementation led to significant improvements in performance quality. There was a noticeable reduction in errors and a decrease in the need for ongoing adjustments, which positively impacted customer satisfaction and increased alignment with technical specifications. In terms of project duration, the results showed that Agile methodology contributed to accelerating execution processes and reducing the time required to complete tasks. Flexibility and responsiveness to changes improved significantly, leading to progress within the set timelines. This improvement was supported by incremental delivery and continuous improvement that are hallmarks of Agile methodology. The study also highlighted that successful Agile implementation requires strong support from senior management, adequate resource provision, and sufficient team training. Additionally, the results emphasized the importance of cross-team collaboration and effective communication in achieving shared goals. Based on these findings, the study offers recommendations for enhancing Agile application in similar projects.